The road to heaven : a book for all who love the truth for the truth's sake . - Messaros, Waldo (Globe Bible Pub. Co., 1888)
"A religious, philosophical, historical and scientific study of God, nature, the soul, the spiritual man, the moral man, the natural man, man as a social and immortal being, his virtues, vices, affections, hopes, aspirations, aims, and destiny, and a hand-book for all who seek that city which hath foundations whose builder and maker is God, the new Pilgrim's progress for the millions whose faces are turned to the sunrise shore where there is no night."